ANALISIS PERSEPSI GURU TERHADAP GAYA KEPIMPINAN KEPALA SEKOLAH SDN 28 SUNGAI LANSEK KABUPATEN SIJUNJUNG - Razef Zulkarnain; Nurhizrah Gistituati; Rusdinal (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
This article analyzes teachers’ perceptions of the principal’s leadership style at Public Elementary School 28 in Sungai Lansak, Sijunjung. The study was conducted in 2021 using a quantitative descriptive analysis method. The results indicated that the principal’s leadership was reflected through four dimensions of Transformational Leadership Theory: idealized influence, intellectual stimulation, inspirational motivation, and individualized consideration. Data analysis showed that teachers perceived the principal’s leadership style as very good across all four dimensions. The findings suggest that effective transformational leadership positively shapes teachers’ perceptions and supports school management.